Systematic Literatur Review : Pengaruh Penggunaan Aplikasi Geometer’s Sketchpad Pada Pembelajaran Matematika SMP - Sri Rezeki; Yahfizham Yahfizham (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
. Geometer's Sketchpad is a maths lesson programme that offers educational material on a variety of subjects, including geometry, algebra, calculus, and other areas of mathematics. The form of research is Systematic Literature Review. Data collection in this method by searching for various journals from national and international journals on Google Scholar and Publish or Perish around 6 journals from 2019 to 2023. Through the results of previous studies in the charts, it should be deducted that the Geometr's Sketchpad application in learning mathematics is very influential because by using Geometr's Sketchpad application is able to provide an increase in students' conceptual understanding ability and is able to increase student activeness.